ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL - Khristina Sri Prihatin (FKIP, Universitas Banten Jaya, 2019)
The objectives of this research to make compare the finance performance between Islamic Commercial Banks and Conventional Commercial Banks in Indonesia in the period 2012-2016 by using financial ratios. Financial ratios are used consisting of CAR, KAP, NPL,and ROA. The purpose of this research is to find out whether there is a difference between the performance of Islamic bank financial statements when compared to conventional banks as a wholeAnalytical techniques used to see comparison of financial performance of Islamic Commercial Banks with Conventional Commercial Bank is the quantitative method that use spss. The analysis showed that there are significant differences for each financial ratio between Islamic Commercial Banks and Conventional Commercial Banks in Indonesia. Islamic Commercial Banks has better performance in terms of LDR ratios, while the Conventional Commercial Banks better performance in terms of the CAR, KAP, NPL, and ROA.